A C‐type lectin with a single carbohydrate‐recognition domain involved in the innate immune response of Tribolium castaneum. Issue 5 (26th March 2019) - Bi, J.; Feng, F.; Li, J.; Mao, J.; Ning, M.; Song, X.; Xie, J.; Tang, J.; Li, B.
Abstract: C‐type lectins are one of the pattern‐recognition proteins involved in innate immunity in invertebrates. Although there are 16 C‐type lectin genes that have been identified in the genome of Tribolium castaneum, their functions and mechanisms in innate immunity remain unknown. Here, we identified one C‐type lectin orthologue, TcCTL6 (TC003708), by sequencing random clones from the cDNA library of the coleopteran beetle, T. castaneum . TcCTL6 contains a 654 bp open reading frame encoding a protein of 217 amino acids that includes a single carbohydrate‐recognition domain. The expression of TcCTL6 was significantly induced by Escherichia coli, Staphylococcus aureus and stimulation with carbohydrates, including lipopolysaccharide and peptidoglycan. A binding assay suggested that the recombinant TcCTL6 not only bound to lipopolysaccharide and peptidoglycan but also bound to Gram‐positive ( S. aureus, Bacillus subtilis and Bacillus thuringiensis ) and Gram‐negative bacteria ( E. coli and Pseudomonas aeruginosa ) in the presence of calcium ions. Furthermore, when TcCTL6 was knocked down by RNA interference, four antimicrobial peptides ( attacin1, attacin2, coleoptericin1 and coleoptericin2 ) were significantly decreased. These results demonstrate that TcCTL6 plays a vital role in the immune response towards pathogen infection by influencing the expression of antimicrobial peptides and the agglutination of bacteria in the presence of calcium ions in T. castaneum .